Reexamine the incremental value of corporate governance mechanisms in emerging markets: Are they really improving firm performance? - Boonyanet, Wachira (Archives of Business Research, 2019)
This study reinvestigates whether corporate governance (CG) mechanisms promote corporate performance. Unlike previous studies that devised their own criteria for measuring CG mechanisms and employed only limited corporate governance mechanisms, this study introduces CG proxies that are publicly available and uses all OECD Corporate Governance’s mechanisms including rights of shareholders, equitable treatment of shareholders, roles of shareholders, disclosure and transparency and responsibilities of board. In addition, the study measures firm performance in three dimensions including Tobin’ Q, ROA and ROE. Using an emerging market – the Stock Exchange of Thailand dataset for the long-range period from 2009 to 2016, the analysis shows that corporate governance mechanisms slightly promote firm performance. Rather, it was found that basic financial information including firm size sale growth and cash dividend payment are significantly correlated with firm performance. However, it seems that the most corporate governance mechanism influences firm performance is annual general meeting (AGM). This means if shareholders fully active their right to control board of directors, this will improve firm performance, not all corporate governance mechanisms would improve firm performance. Finally, Tobin’s is the most measuring tools comparing with ROA and ROE.